2009
DOI: 10.1590/s1516-89132009000500026
|View full text |Cite
|
Sign up to set email alerts
|

Ionizing radiation effects on food vitamins: a review

Abstract: Ionizing radiation has been widely used in industrial processes, especially in the sterilization of medicals, pharmaceuticals, cosmetic products, and in food processing. Similar to other techniques of food processing, irradiation can induce certain alterations that can modify both the chemical composition and the nutritional value of foods. These changes depend on the food composition, the irradiation dose and factors such as temperature and presence or absence of oxygen in the irradiating environment. The sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(52 citation statements)
references
References 51 publications
0
42
0
1
Order By: Relevance
“…Furthermore, the remaining vitamers decreased in irradiated or stored samples, probably due to oxidative processes. Tocopherols (vitamin E) were already reported as sensitive to radiation, being their losses during the irradiation often substantial (Dionísio et al 2009). …”
Section: Deliciosusmentioning
confidence: 99%
“…Furthermore, the remaining vitamers decreased in irradiated or stored samples, probably due to oxidative processes. Tocopherols (vitamin E) were already reported as sensitive to radiation, being their losses during the irradiation often substantial (Dionísio et al 2009). …”
Section: Deliciosusmentioning
confidence: 99%
“…Ionizing radiation holds great potential for extending the shelf life of food commodities as it can eliminate pathogenic bacteria, disinfest fresh fruits and vegetables as a postharvest quarantine treatment and reduce or eliminate microorganisms. This technique has advantages over other techniques because gamma radiation presents effective and homogeneous penetration power in the tissue, requires a relatively short radiation time and does not increase the temperature of the fruit ( DIONÍSIO et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, storage effects were higher than irradiation effects. Dionísio et al (2009) demonstrated that, Strawberries (Shasta variety, Fragaria sp.) submitted to 1.0-2.0 kGy doses did not show any significant decrease in vitamin C levels during two and 11 days of storage at 5°C.…”
Section: Vitaminsmentioning
confidence: 99%
“…However these maximum values depend on the type of products and might modify with new, resistant cultivars (Zhu, et al, 2009). For example, some salad vegetables could resist up to 4000 Gy without physical-chemical damages and considerable quality loss (Nunes et al, 2008) whereas, for some products, such as lettuce leaves and apple fruit (Gala and Fuji variety) radiation doses should not exceed 600 Gy (Dionísio et al, 2009;Niemira et al, 2002).…”
Section: Fruits and Vegetablesmentioning
confidence: 99%